Interesting thermal variations owing to cationic ring structural features in protic ionic liquids - Rai, Gitanjali; Kumar, Anil (Physical Chemistry Chemical Physics, 2013)
The present communication divulges interesting thermal behavior of different protic ionic liquids arising due to the hydrophobicity modifications in their parent cationic ring structures. This work assists us in differentiating between protic ionic liquids, their aprotic counterparts and common electrolytes in water. The thermal signatures produced by protic ionic liquids, aprotic ionic liquids and electrolytes emerge as individual fingerprints for them.